PENGARUH STATUS KESEHATAN DAN MOTIVASI KESEHATAN MOTIVASI KESEHATAN PADA KEPUTUSAN BEROBAT YANG DI 1 MEDIASI KETERLIBATAN - Liska Claudia Tanesib; Waluyo Budi Atmoko; Ariefah Yulandari (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2020)
his study aims to examine treatment decisions that are influenced by health status and health motivation mediated by involvement. the influence of health status and health motivation and mediated involvement will influence Consumer treatment decisions. Data obtained through a questionnaire distributed to consumers in Surakarta in a cluster. The sampling technique used was pur posive sampling of 200 respondents. Hypothesis testing uses Structural Equation Modeling (SEM) analysis. The results showed a positive health status on involvement, health motivation does not have a positive effect on in volvement, involvement has a positive effect on treatment decisions.